2012
DOI: 10.1186/1756-0500-5-376
|View full text |Cite
|
Sign up to set email alerts
|

Luminal A and luminal B (HER2 negative) subtypes of breast cancer consist of a mixture of tumors with different genotype

Abstract: BackgroundThe St Gallen International Expert Consensus 2011 has proposed a new classification system for breast cancer. The purpose of this study was to elucidate the relationship between the breast cancer subtypes determined by the new classification system and genomic characteristics.MethodsInvasive breast cancers (n = 363) were immunohistochemically classified as follows: 111 (30.6%) as luminal A, 95 (26.2%) as luminal B (HER2 negative), 69 (19.0%) as luminal B (HER2 positive), 41 (11.3%) as HER2, and 47 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 32 publications
5
55
2
Order By: Relevance
“…The only patient among the Luminal group exhibiting cCR had the Luminal B HER2 negative subtype. This heterogeneity of response to chemotherapy is in consistence with the genomic heterogeneity reported for the Luminal A and Luminal B types of breast cancers (Yanagawa et al, 2012). Lack of efficacy of neoadjuvant chemotherapy in patients with ER positive tumors and Luminal A tumors is well documented (Carey et al, 2007;Colleoni et al, 2009;Lv et al, 2011) and the use of adjuvant chemotherapy has been debated in the Luminal A subclass of patients with early breast cancer (Coates et al, 2012) and IX trials found no benefit of adding chemotherapy in patients with ER positive disease (Aebi et al, 2011;Karlsson et al, 2011).…”
Section: Discussionsupporting
confidence: 66%
“…The only patient among the Luminal group exhibiting cCR had the Luminal B HER2 negative subtype. This heterogeneity of response to chemotherapy is in consistence with the genomic heterogeneity reported for the Luminal A and Luminal B types of breast cancers (Yanagawa et al, 2012). Lack of efficacy of neoadjuvant chemotherapy in patients with ER positive tumors and Luminal A tumors is well documented (Carey et al, 2007;Colleoni et al, 2009;Lv et al, 2011) and the use of adjuvant chemotherapy has been debated in the Luminal A subclass of patients with early breast cancer (Coates et al, 2012) and IX trials found no benefit of adding chemotherapy in patients with ER positive disease (Aebi et al, 2011;Karlsson et al, 2011).…”
Section: Discussionsupporting
confidence: 66%
“…Hence, suitable classification is needed for appropriate individual management (9-11). Currently due to the inadequate prognostic power and predictive accuracy of existing classifications, a modified classification according to molecular characteristics of breast cancer was defined by the 13 th St. Gallen Breast Cancer Conference to categorize breast cancers into molecular subtypes (1). Despite the lack of a complete overlap among molecular classes and their immunohistochemical status, the St. the patients in our study had luminal A and B molecular subtypes (78%) and only 13% had triple-negative breast cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Molecular subtypes were defined as follows: Luminal A: ER+, PR+, HER2-, and low Ki-67 index; luminal B (HER2-): ER+, PR+ or PR-, HER2-, and high Ki-67 index; luminal B (HER2+): ER+, PR+, HER2+; HER2: ER-, PR-, HER2+; and triple-negative: ER-, PR-, HER2-. In our study, the Ki-67 index was scored as high when 14% or more of the tumor cells were immunohistostained in accordance with the St. Gallen International Expert Consensus guidelines (1). Immunohistochemistry results were taken from the reports and recorded.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The number of molecular designations for the breast cancer subtypes have increased recently, nonetheless the core groupings continue to be luminal A, luminal B, HER2+, Basal-like breast cancer (BLBC) and triple negative breast cancer (TNBC) (1,2). Luminal A are characterized as positive for estrogen receptor gene (ER+) and progesterone receptor (PR+), and human epidermal growth factor receptor 2negative (HER2-).…”
Section: Introductionmentioning
confidence: 99%